A New Narrative for CO2 Corrosion of Mild Steel. Issue 11 (26th March 2019) - Kahyarian, Aria; Nesic, Srdjan
Abstract : The conventionally accepted mechanism of CO2 corrosion considers the direct reduction of carbonic acid as the main process that results in the higher corrosion rates as compared to that observed in strong acid solutions with the same pH. The present study is an attempt to further elucidate the underlying electrochemical mechanisms of CO2 corrosion. In this regard, the mechanism of CO2 corrosion was investigated based on the cathodic and anodic polarization behavior of mild steel in CO2 -saturated solutions at elevated pressures. The examination of charge transfer controlled cathodic currents showed that the direct reduction of carbonic acid is insignificant at the condition of the present study. Additionally, the iron dissolution reaction was found to be significantly affected by the presence of CO2, particularly over the transition and pre-passivation ranges. A comprehensive mathematical model based on the presented mechanistic understanding of the system was developed and used for further quantitative examinations. The present mechanistic model was shown to be able to represent the main mechanistic features of polarization curves and predict the corrosion rates with reasonable accuracy.